2017
DOI: 10.1017/s0033291716003354
|View full text |Cite
|
Sign up to set email alerts
|

Neural indicators of interpersonal anger as cause and consequence of combat training stress symptoms

Abstract: Results suggest that during anger-provoking social interactions, flawed vmPFC functionality may serve as a causal risk factor for the development of stress symptoms, and heightened reactivity of the LC possibly reflects a consequence of stress-inducing combat training. These findings provide potential neural targets for therapeutic intervention and inoculation for stress-related psychopathological manifestations of anger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 73 publications
1
22
1
Order By: Relevance
“…This sample is similar to that reported in Gilam et al (2017). Participants were recruited to the study during the first 2 weeks after military service enlistment.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…This sample is similar to that reported in Gilam et al (2017). Participants were recruited to the study during the first 2 weeks after military service enlistment.…”
Section: Methodssupporting
confidence: 92%
“…Further support for the relation between vigilance and anger is gained from a recent study showing the high locus coeruleus (LC) activity to interpersonal anger induced by a modified ultimatum game was associated with less anger regulation (Gilam et al, 2015). In fact, it has been recently shown that an increase in this LC activation during interpersonal anger following chronic stress was associated with the manifestation of PTSS (Gilam et al, 2017). Moreover, PTSD patients have increased LC activation during direct vs. averted eye-to-eye contact, which may be perceived as threat (Steuwe et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found that activation of the locus coeruleus, an important structure in the hormone cascade associated with the autonomic stress response, is linked specifically to aggression 138,139 . It is hypothesized that locus coeruleus activity helps to orient attention to salient information and that changes to activity within this region may alter threat reactivity 140 .…”
Section: Altered Arousal and Reactivitymentioning
confidence: 99%
“…Orbitofrontal cortex dysfunction in particular has been linked to aggressive and/or impulsive behaviour 146148 . Specifically, in PTSD there is empirical evidence of differential activity in the orbitofrontal cortex, vmPFC and locus coeruleus in anger-related paradigms 140,142 .…”
Section: Altered Arousal and Reactivitymentioning
confidence: 99%
“…Since the specific infantry unit recruits only male soldiers, participants in this study were only male. The soldiers were at the beginning of an intense combat-training period of 1 year which was subsequently shown to increase traumatic stress symptoms (TSS) levels (Gilam et al, 2017 ). The civilians had no change in TSS along a similar period of civil-service.…”
Section: Introductionmentioning
confidence: 99%